"Y de esta manera quedaron todos los hombres sin mujeres": el mestizaje como estrategia de colonización en la Española (1501-1503) (Revista de Crítica Literaria Latinoamericana, 2011)
This article focuses on mestizaje in the colonization of Hispaniola, especially in relation with Nicolás de Ovando's settlements (1501-1503). From a Colonial Studies perspective, this paper seeks to dialogue with recent research in archaeological Contact Studies that have focused on the problem of gender. The analysis from mestizaje allows us to think of Hispaniola as a gender and race contact zone in the frame of the relations of power and domination imposed by Spanish conquest. Through the discursive analysis of the Instructions that the Crown sent to Ovando and a reading of the myth of Guahayona as recorded by Ramón Pané in his Relación de las antigüedades de los indios (1498), I analyze the role of gender relations in the establishment of the colonial power relation in order to open new reflection on the central place of gerden in the processes of colonial subordination that follow this initial stage.
Keywords: Mestizaje; Hispaniola; Contact; Gender; Tainos; Ramón Pané